Communication Strategies by Indonesian EFL Learners in English Conversation Class - Agus Wijayanto; Diyah Murti Hastuti (JURNAL ARBITRER, 2021)
To be able to conduct smooth communication has been the focus of teaching and learning L2. Since the late 1970s, developing language learners' communicative competence has become the center of L2 teaching. This paper is part of a study investigating how elementary-level English learners at an English course in Surakarta-Indonesia conduct English conversations. It particularly observes how they use communication strategies. The data was obtained through recording the conversations between instructors and the learners in teaching and learning activities. This study revealed that the learners frequently used stalling or time gaining when communicating their ideas or opinions. Assertive was the dominant speech act used by the learners, whereas expressive was the least. This could be because during the learning process, the learners were the ones who answered questions and expressed ideas in response to the instructors' questions.